2017
DOI: 10.21037/cdt.2017.08.16
|View full text |Cite
|
Sign up to set email alerts
|

Clinical outcomes of PCSK9Is: a meta-analysis of randomized clinical trials

Abstract: PCSK9Is should be strongly considered to improve clinical outcomes in patients at high risk for atherosclerotic CVD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…Moreover, an important regression of atheroma plaque volume was observed after 76 weeks of evolocumab treatment in about 2/3 of patients [ 40 ]. The treatment with PCSK9 inhibitors was associated with a lower number of major adverse cardiovascular events, coronary revascularization, and myocardial infarction, but had no effect on mortality [ 94 ]. A highly durable RNA interference therapeutic inhibitor of PCSK9 synthesis is being tested.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, an important regression of atheroma plaque volume was observed after 76 weeks of evolocumab treatment in about 2/3 of patients [ 40 ]. The treatment with PCSK9 inhibitors was associated with a lower number of major adverse cardiovascular events, coronary revascularization, and myocardial infarction, but had no effect on mortality [ 94 ]. A highly durable RNA interference therapeutic inhibitor of PCSK9 synthesis is being tested.…”
Section: Discussionmentioning
confidence: 99%
“…A large meta-analysis that included 62,776 patients from 6 randomized clinical trials found that treatment with PCSK9 inhibitors was associated with a lower number of major adverse cardiovascular events, coronary revascularization, and myocardial infarction, but had no effect on mortality. These are arguments for their use in patients with a high risk of ischemic heart disease [ 94 ]. A highly durable RNA interference therapeutic inhibitor of PCSK9 synthesis is being tested.…”
Section: Therapeutic Aspectsmentioning
confidence: 99%
“…Though statins are effective in reducing adverse cardiovascular outcomes, the need to address substantial residual cardiovascular disease risk among statin-treated individuals has led to the development of new injectable pharmacotherapies such as proprotein convertase subtilisin/kexin type 9 (PCSK9) or angiopoietin like 3 (ANGPTL3) modulating drugs (5,6). There is strong evidence that these agents are clinically effective (7), but they are currently not considered cost effective due to their high price tag and the high prevalence of cardiovascular disease secondary to hyperlipidemia-and hence eligibility for lipid-reducing therapy in the US population. (8) Thus, there exists a pressing need for new drugs to prevent ASCVD, especially if new drugs could be discovered more economically or targeted to new patient subsets (9,10).…”
Section: Introductionmentioning
confidence: 99%